Calcium in saliva and impact on health - (:unkn) unknown (Royal Society of Chemistry, 2016)
Saliva is an oral fluid with a protective role in oral health maintenance. Saliva consists of inorganic and organic compounds and calcium is one of the inorganic components. Calcium, which is the fifth most abundant element in the human body, plays a key role in bone mineralization, in addition to its many other biological functions. It plays a crucial role in the physiological function of both excitable and nonexcitable cells. Beneficial effects of saliva are derived from the cleansing action of salivary flow and from interaction and exchange of the chemical constituents between the saliva and the dental enamel. Proteins such as statherin, proline-rich proteins and mucins prevent calcium precipitation and keep the calcium concentration supersaturated in saliva in order to prevent enamel demineralization. Due to its affinity for being easily taken up by plaque, salivary calcium, is an important factor, not only with regard to the onset of periodontitis but also significantly with regard to oral health. In this chapter, the effects of salivary calcium on oral and dental health have been reviewed. © 2016 The Royal Society of Chemistry.